2015
DOI: 10.5152/iao.2014.250
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mean Platelet Volume in Patients with Bell’s Palsy

Abstract: OBJECTIVE:The aim of this study is to investigate the mean platelet volume (MPV) levels in patients with Bell palsy (BP). Moreover, we aimed to find out any correlation between MPV levels and the severity and prognosis of BP. MATERIALS and METHODS:The study group consisted of 30 subjects who presented with BP and 30 control subjects with no evidence of facial nerve pathology. The evaluation of subjects included a detailed history, general physical examination, and assessment of laboratory blood parameters. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…In another study, MPV was found to be high in patients with BP. As a result of that study, the authors concluded that higher MPV values would be a predictor marker for the severity and prognosis of BP [18]. In our study, we did not find higher MPV and PLR values in BP patients than in those controls.…”
contrasting
confidence: 67%
“…In another study, MPV was found to be high in patients with BP. As a result of that study, the authors concluded that higher MPV values would be a predictor marker for the severity and prognosis of BP [18]. In our study, we did not find higher MPV and PLR values in BP patients than in those controls.…”
contrasting
confidence: 67%
“…Additionally, they had showed that there was positive correlation between PDW and MPV values with grade of facial paralysis. However, they had reported that there was no correlation between MPV and PDW values and prognosis of facial paralysis [18]. In contrast, Kum et al [4] had reported no correlation with between the MPV value and grade of facial paralysis.…”
Section: Discussionmentioning
confidence: 98%
“…Platelets with a large volume have been showed to be metabolically and enzymatically more active and more tendencies to aggregation compared with the small ones [15][16][17]. Özler et al [18] had showed that the MPV and the PDW values in patients with Bell palsy were higher. Additionally, they had showed that there was positive correlation between PDW and MPV values with grade of facial paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that NLR levels are highly correlated with BP prognosis [ 32 , 38 ]; certain studies have reported a higher NLR in BP patients experiencing poor outcomes [ 38 ], a positive correlation between NLR and disease severity [ 14 , 33 , 36 , 56 ], and longer recovery times in patients with a higher NLR [ 25 ]. Additionally, facial nerve contrast enhancement was confirmed by MRI in patients with a high NLR [ 36 ].…”
Section: Prognostic Biomarkers In Apfpmentioning
confidence: 99%
“…Considering the above-mentioned etiologic factors of APFP development, a laboratory test that evaluates prognosis is considered desirable. Numerous studies have investigated hematologic markers based on inflammatory mediators, vascular failure, oxidative stress, and immunological responses [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%